From hacking the human genome to editing organs - Tobita, Takamasa (Organogenesis, 2015)
In the recent decades, human genome engineering has been one of the major interesting research subjects, essentially because it raises new possibilities for personalized medicine and biotechnologies. With the development of engineered nucleases such as the Zinc Finger Nucleases (ZFNs), the Transcription activator-like effector nucleases (TALENs) and more recently the Clustered Regularly Interspaced short Palindromic Repeats (CRISPR), the field of human genome edition has evolved very rapidly. Every new genetic tool is broadening the scope of applications on human tissues, even before we can completely master each of these tools. In this review, we will present the recent advances regarding human genome edition tools, we will discuss the numerous implications they have in research and medicine, and we will mention the limits and concerns about such technologies